PENGGARUH PENGGUNAAN APLIKASI QUIZIZZ TERHADAP MOTIVASI BELAJAR SISWA KELAS V SD NEGERI BANJARANYAR 02 - Aryanti, Yussri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At the Elementary School (SD) level, one of the challenges faced is creating a learning environment that can motivate students to be actively involved in every learning activity. In this study, the author will examine the effect of game media in the Quizizz application to increase student learning motivation. The approach used in this study is Research and Development (R&D) in the development and testing of the effectiveness of the application in increasing student learning motivation through the ADDIE model. The subjects of this study were 26 fourth-grade students of Banjaranyar 02 Elementary School consisting of 9 male students and 17 female students as the experimental class and 23 fourth-grade students of Banjaranayar 03 Elementary School consisting of 10 male students and 13 female students as the control class. Research Results Based on the results of observations made, it can be concluded that the achievement level of 60.05% was in the less effective category at meeting I. At meeting II, 70.05% was in the effective category. It can be concluded that the implementation of the learning process using the Quizizz application can be seen from the increase in the percentage obtained.